Apolipoprotein epsilon 4 genotype is associated with less improvement in cognitive function five years after cardiac surgery: a retrospective cohort study - Bartels, Karsten (Can J Anaesth, 2015)
PURPOSE: Cognitive performance after cardiac surgery can be impaired, and genetic risk factors have previously been suggested. When compared with other isoforms of the gene, the apolipoprotein epsilon 4 (APOE4) allele is associated with worse outcomes in many neurologic disorders. We hypothesized that the APOE4 allele is associated with less favourable cognitive function five years after surgery. METHODS: Caucasian patients enrolled in previously reported prospective cognitive trials in both cardiac and non-cardiac surgery participated in this retrospective cohort study. Neuropsychological function was assessed at baseline and five years postoperatively. The relationship between change in cognitive index score and APOE was evaluated using multivariable linear regression. An additive genetic model toward the epsilon 4 allele was applied with adjustment for baseline cognition, years of education, age, presence of diabetes in both cohorts, and presence of coronary artery disease in the non-cardiac surgery cohort. RESULTS: A total of 357 patients were included in this study. In the cardiac surgery group (n = 233), baseline cognitive index (P < 0.001), years of education (P = 0.04), age at time of surgery (P < 0.001), and the APOE4 allele (P = 0.009), were associated with a five-year change in cognitive index. Patients carrying the APOE4 allele showed less improvement in cognitive index scores five years after cardiac surgery compared with patients without the APOE4 allele. In the non-cardiac surgery (n = 124) group, no association was found between APOE4 allele status and change in cognitive index. CONCLUSION: We report an association between APOE4 and neurocognitive function five years following cardiac surgery. Preoperative identification of patients with the APOE4 genotype may improve stratification of cardiac surgery patients at risk for a less favourable cognitive trajectory.